2016
DOI: 10.1116/1.4941366
|View full text |Cite
|
Sign up to set email alerts
|

Reduce the matrix effect in biological tissue imaging using dynamic reactive ionization and gas cluster ion beams

Abstract: In the context of a secondary ion mass spectrometry (SIMS) experiment, dynamic reactive ionization (DRI) involves introducing a reactive dopant, HCl, into an Ar gas cluster primary ion beam along with a source of water to enable dissociation of HCl to free protons. This concerted effect, precisely occurring at the impact site of the cluster beam, enhances the protonation of molecular species. Here, the authors apply this methodology to study the hippocampus and cerebellum region of a frozen-hydrated mouse brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Ar n + shows 50% enhancement of m/z 707/325, which is the ratio of ion [2M + Na] + to [M + H – H 2 O] + . We have previously noted that the response of sodiated species can vary extensively, depending upon the nature of the projectile [20, 32]. Overall, the studies on these three model compounds suggest that the SIMS spectra associated with Ar n + or (CO 2 ) n + are closely aligned.…”
Section: Resultsmentioning
confidence: 71%
“…Ar n + shows 50% enhancement of m/z 707/325, which is the ratio of ion [2M + Na] + to [M + H – H 2 O] + . We have previously noted that the response of sodiated species can vary extensively, depending upon the nature of the projectile [20, 32]. Overall, the studies on these three model compounds suggest that the SIMS spectra associated with Ar n + or (CO 2 ) n + are closely aligned.…”
Section: Resultsmentioning
confidence: 71%
“…In particular the role that the chemical composition of the polyatomic projectile, and its distinctive sputtering dynamics play in matrix ionisation effects has yet to be determined. Cluster ion beams such as C 24 H 12, (H 2 O) n , HCl‐doped Ar n , CH 4 ‐doped Ar n or water‐doped Ar n provide potentially reactive species such as protons, which in addition to increasing overall ionisation yields, might influence the suppression/enhancement effects in mixed samples. Biddulph et al showed that switching from Au to C 60 or C 24 H 12 primary ions ameliorated the matrix effects in the analysis of mixtures of 2,4,6‐trihydroxyacetophenone (THAP) with cytosine and THAP with barbituric acid (BA) .…”
Section: Introductionmentioning
confidence: 99%
“…(H 2 O) 6000 and (Ar/H 2 O) 2000 , the cholesterol intensity was shown to be similar in the two regions, more closely representing the actual in vivo concentrations, whereas, in the analysis with Ar 2000 , cholesterol was hardly detected in the grey matter . In another study on brain tissue, Tian et al applied a dynamic reactive ionisation (DRI) approach in which HCl was doped into an Ar n cluster ion beam accompanied by supplying the sample with H 2 O/D 2 O vapour . The water‐mediated surface acid‐dissociation resulted in increased protonated lipid signals and reduced matrix effects compared with Ar n projectiles.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we have shown that the ionization probability can be increased by more than an order of magnitude, reaching levels comparable to those produced by the H 2 O cluster ion source or by a C 60 + ion source. Moreover, DRI has been shown to reduce salt suppression of molecular ions in complex biological tissue [18]. …”
Section: Introductionmentioning
confidence: 99%